Integration of LED-based lighting in academic buildings for energy efficiency considerations - Mohamad Zhafran Hussin; Saiful Firdaus Abdul Shukor; Nor Diyana Md Sin; Yusrina Yusof; Muhammad Zairil Muhammad Nor; Noor Hasliza Abdul Rahman (Institute of Advanced Engineering and Science, 2021)
This paper presents an assessment by integration of LED T8 tube lamps in academic buildings for energy efficiency considerations. The proposed project was implemented in conjunction with a national mission, national energy efficiency action plan (NEEAP) for 10-year implementation period of 2016-2025 in reducing allocation on subsidies for efficient expenditure towards energy-saving measures. A case of study in a real environment at one of the UiTM’s buildings as a target task area has been tested by replacing a LED lighting technology in consideration of current operating costs and power factor performances. From the results, LED T8 tubes have shown a better power factor of 0.89 compared to fluorescent lamps with about 0.61 and primarily driven by economic benefits in terms of cost savings of up to 50% with return-on-investment (ROI) 6 months after installation. By integrating this technology, nearly 50% of the total energy consumption in indoor lighting system could be significantly saved, thus reducing the total cost of electricity bills in the future within the target area.